The Effect of Diamond Passing Training Model on Passing Accuracy in Soccer School Students - Ferdi Fahrus Syaehan; Imam Hariadi (STKIP Paasundan Press, 2025)
This study aims to determine the effect of diamond passing training model on passing accuracy in students at SSB Tunjung Sekar. Using a quantitative approach with a pre-experimental method, this study used a one group pretest-posttest design. The population and sample in the study were 20 SSB Tunjung Sekar students selected by simple random sampling through a lottery system. Data was collected using short passing test. Data analysis included normality test, homogeneity test, and paired sample T-test. The findings showed a significant increase in the mean score from 4.50 in the pre-test to 7.89 in the post-test. The significance value of 0.000 from the paired t-test shows a significant effect. It can be concluded that the diamond passing training model significantly improves the passing accuracy of SSB Tunjung Sekar students